2020
DOI: 10.1177/8756972820973082
|View full text |Cite
|
Sign up to set email alerts
|

Agile, Traditional, and Hybrid Approaches to Project Success: Is Hybrid a Poor Second Choice?

Abstract: Three project management approaches—traditional, agile, and hybrid—were considered in this study. Results from an international study, including 477 cross-industry projects, indicated that 52% of projects could be categorized as hybrid approaches. A regression analysis using multiple outcome measures indicated substantial explanatory power (0.21 < R 2 <0.41). Analysis suggested that hybrid and agile approaches significantly increase stakeholder success over traditional approaches while achieving the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 69 publications
(110 reference statements)
2
66
0
10
Order By: Relevance
“…Hybrid models combine agile methods with traditional product development models [15,39], thus enabling companies to take advantage of agility without sacrificing the stability provided by traditional approaches [15,16]. Many researchers agree that it is the balance between agile and traditional approaches that is usually the most effective for managing projects [29,[40][41][42]. A study by Gemino et al showed that hybrid approaches lead to higher stakeholder satisfaction than traditional approaches while allowing for a comparable project efficiency as completely agile approaches [41].…”
Section: Hybrid Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid models combine agile methods with traditional product development models [15,39], thus enabling companies to take advantage of agility without sacrificing the stability provided by traditional approaches [15,16]. Many researchers agree that it is the balance between agile and traditional approaches that is usually the most effective for managing projects [29,[40][41][42]. A study by Gemino et al showed that hybrid approaches lead to higher stakeholder satisfaction than traditional approaches while allowing for a comparable project efficiency as completely agile approaches [41].…”
Section: Hybrid Modelsmentioning
confidence: 99%
“…Many researchers agree that it is the balance between agile and traditional approaches that is usually the most effective for managing projects [29,[40][41][42]. A study by Gemino et al showed that hybrid approaches lead to higher stakeholder satisfaction than traditional approaches while allowing for a comparable project efficiency as completely agile approaches [41].…”
Section: Hybrid Modelsmentioning
confidence: 99%
“…Also, different meanings and connotation are associated with the same thing, which increases the confusion for team members who are set-out to select either of the methodology. Consequently, the combination of Agile and Waterfall in a project can only be validated through empirical studies and practice (Gemino, Horner Reich & Serrador, 2021).…”
Section: Managing Traditional and Agile Software Developmentmentioning
confidence: 99%
“…Pendekatan ini sejatinya sudah banyak diterapkan pada banyak perusahaan secara global. Bahkan banyak diantara mereka yang memang sengaja menerapkan pendekatan hibrida dan sudah menerapkannya dalam jangka waktu lama (Gemino, Reich, & Serrador, 2020).…”
unclassified